Public procurement of local food in European Union law - Kapała, Anna (Przegląd Prawa Rolnego, 2022)
The aim of these considerations is to answer the question to what extent EU public procurement regulations allow contract award criteria that would enable the supply of food locally produced or sourced from short supply chains. Directive 2014/24/EU on public procurement provides for the use of criteria that include environmental, quality or social aspects in order to ensure the most cost-effective tenders. The inclusion of these aspects determines “green” or “sustainable” procurements. Among the qualitative and environmental aspects, criteria such as products from short chains or direct supplies may be specified, allowing local food to be the subject of “green” and “sustainable” public procurement.